تحليل الأخطاء الإملائية في كتابة اللغة العربية في الصف الوسطى بالمدرسة الدينية الإسلامية "الفردوس" فوروادادي كديري - Aprilia, Nurul Fitria; Hariyanto, Juni; Zuhriyah, Nunik (Al-Fakkaar, 2024)
The skill of writing good and correct is indispensable to get spelling which is in accordance with the rules. Spelling error appear because the student not yet mastered the four skill speaking. Other than that learning Arabic language still considered complicated by some students. There were some problem formulations in this research, those were: 1) What were spelling error on Arabic writing those experienced by Wustho degree students in MADIN Al Firdaus Purwodadi Kediri? 2) What were the causes of Arabic spelling error those experienced by wustho degree students in MADIN Al Firdaus Purwodadi Kediri? 3) What were the analisys of spelling error in arabic made by wustho degree students and what is the teacher effort in correcting spelling errors? And this research was supposed to identify, to classify, to analyze Arabic dictation inaccuracy, and identify teacher effort to redress the mistakes. In this research, researcher used descriptive qualitative approach because there’s no numeral data utilized. However, relevant and detailed literatures could serve informative result. The result of the research showed that there are some spelling error, those are vowels, hamzah (ء), alif lam (ال) syamsiyah qomariyah, process of writing Ta’ (ة), and long vowels (؅). There are some causes of the chase, are: intralingua or the complexity of the target language, less accuracy or less notification of the teachers and students, than the students don’t like Arabic lesson. Motivating students to learn Arabic language, correcting error part on Arabic lesson, and attending more Arabic activities are some endeavours to increase student passion on learning Arabic language.